Progress to Clarify How NOTCH3 Mutations Lead to CADASIL, a Hereditary Cerebral Small Vessel Disease - Ikuko Mizuta; Yumiko Nakao-Azuma; Hideki Yoshida; Masamitsu Yamaguchi; Toshiki Mizuno (Biomolecules, 2024)
Notch signaling is conserved in C. elegans, Drosophila, and mammals. Among the four NOTCH genes in humans, NOTCH1, NOTCH2, and NOTCH3 are known to cause monogenic hereditary disorders. Most NOTCH-related disorders are congenital and caused by a gain or loss of Notch signaling activity. In contrast, cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) caused by NOTCH3 is adult-onset and considered to be caused by accumulation of the mutant NOTCH3 extracellular domain (N3ECD) and, possibly, by an impairment in Notch signaling. Pathophysiological processes following mutant N3ECD accumulation have been intensively investigated; however, the process leading to N3ECD accumulation and its association with canonical NOTCH3 signaling remain unknown. We reviewed the progress in clarifying the pathophysiological process involving mutant NOTCH3.